TRADISI DAN MAKNA DOA ROSARIO BAGI UMAT WILAYAH ROHANI SANTO ANSELMUS PADA GEREJA KATOLIK PAROKI SANTO FRANSISKUS XAVERIUS DI DESA GUAAN - Rindyani Katarina Singal (Universitas Sam Ratulangi, 2023)
Church / Church Teaching as part of the living of the Christian faith by involving all Catholic Christians. This devotion to Our Lady is carried out in various ways including the Rosary, Triple Novena, Hail Mary, and Pilgrimage to the Cave of Mary. The most popular and prominent is the Rosary. The Rosary is known as one of the inner prayers. Therefore, the Rosary becomes the most effective means of contemplation to develop among the faithful a commitment to contemplation of the Christian mystery as an exercise in true holiness. The tradition of the Rosary is carried out in May and October, and the people involved range from children to adults. In carrying out this tradition, people do it by visiting house to house or from one family to another. By praying the Rosary people are sent to reach Christ, so that people not only arrive at devotion but are sent to arrive at true conversion. The form of respect addressed to Our Lady gives its own distinctive in the Catholic church, especially to the people of the spiritual area of Saint Anselm in Guaan Village. This activity/tradition is sacred because through the Rosary can develop their faith. Keywords: tradition, meaning, prayer of the rosary